Patricians, Knights, or Nobles? Historiography and Social Status in Late Medieval Antwerp - Damen, Mario (The Medieval Low Countries, 2014)
Abstract This article explores the significance of writing history for a late medieval Antwerp patrician family: Van Halmale. In recent historiography, families like the Van Halmales have not received the attention they deserve, in part because their social status is difficult to pin down. Although the Van Halmales had knightly titles and performed deeds of arms on the battlefield and during tournaments, their noble status was not undisputed. Both a chronicle and a tournament diary written by different members of the Van Halmale family reflect the aspirations of a dominant social category in the late medieval towns of Brabant, Flanders, and Holland. Their writings reflect how the Van Halmales perceived themselves and how they wanted their contemporaries and peers to perceive them. In that sense the writing of history was indeed a means for nobles (and would-be-nobles) to justify (or to claim) their privileged position. Their works helped them to express their identity as powerful aldermen, firmly rooted in an urban environment but with open minds for the world of princes and (inter)national politics.